Cyclopentanoid monoterpenes from the whole plant of Rehmannia piasezkii maxim. (November 2022) - Zhou, Jie; Shi, Guoru; Zhang, Wanqi; Li, Li; Chen, Ruoyun; Liu, Yanfei; Yu, Dequan
Abstract: Twelve undescribed cyclopentanoid monoterpenes, Jiopiasins A–K and 6- epi -rehmaglutin A, and 19 known compounds were isolated from the whole plant of Rehmannia piasezkii Maxim. The structures of these compounds, especially their absolute stereochemistry, were established by extensive spectroscopic analysis, various quantum chemical calculations, and/or X-ray diffraction analyses. Furthermore, in vitro assays, some compounds exhibited moderate hepatoprotective activities against N-acetyl-p-aminophenol (APAP)-induced HepG2 cell damage. Graphical abstract: Image 1 Highlights: Twelve undescribed cyclopentanoid monoterpenes were isolated. Their absolute configurations were confirmed by ECD data or X-ray diffraction analyses. Four compounds showed moderate hepatoprotective activity.